(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
The influence dependence of the short circuit and the open circuit voltage, induced by an irradiation, depends on a single parameter , product of the introduction rate of the defects responsible for non radiative recombination times their trapping cross section. This parameter, characteristic of a given material, can be determined experimentally, hence allowing the computation of the degradation for any type of cell or multi-junction cell. The validity of this procedure is demonstrated and illustrated in the case of the degradation of the short circuit current density of GaInP/GaAs (dual-junction) and GaInP/GaAs/Ge (triple-junction) cells. We found that the order of the product is 10-12 cm and 10-13cm for GaAs sub-cell and GaInP sub-cell respectively . إن التأثير المستحث بالتشعيع الإلكتروني على كل من كثافة تيار الدارة المقصورة وجهد الدارة المفتوحة، يتعلق بمتحول وحيد هو ، الذي يمثل جداء معدل تشكل العيوب المسؤولة عن مراكز إعادة الاتحاد غير المشعة في مقاطعها العرضية للاصطياد. هذا المتحول، الذي يميز خصائص مادة ما، يمكن أن يعين تجريبياً، وبالتالي يسمح لنا بحساب التلف لأي نوع من الخلايا الشمسية أو الخلايا الشمسية متعددة الوصلات. تم البرهان على صلاحية تطبيق هذه الطريقة من أجل حالة تلف كثافة تيار الدارة المقصورة للخلايا الشمسية من النوع GaInP/GaAs، GaInP/GaAs/Ge. ونشير إلى أن قيمة الجداء التي وجدناها هي 10-12cm و10-13cm من أجل الخليتين الشمسيتين sub-cell GaAs وsub-cell GaInP على الترتيب .